1870 La. Acts 127 - (:unkn) unknown (My University, 1870)
Persons, Trades, Professions and Occupations Subject to Taxation,§ 3, pt. 6: From each proprietor or keeper of every billiard saloon, bowling alley or pistol gallery, in which there is but one table, alley or target, twenty-five dollars; where there are two tables, alleys or targets, forty dollars; where there are more than two tables, alleys or targets, ten dollars additional on each table, alley or target
Keywords: SHOOTING RANGES OR GALLERIES